Volatility Effectiveness for Selected Penny Stocks in the Indian Stock Market - Bhattacharjee, Sandeep (Indian Journal of Research in Capital Markets, 2025)
Purpose : The study investigated the volatility efficacy of specific penny stocks in the Indian stock market. The research emphasized an urgent need for efficient volatility assessment tools in emerging markets, considering the 78% year-on-year increase in penny stock trading volumes (National Stock Exchange of India, 2023) and considering 43% of Indian traders possess these high-risk instruments (Zerodha, 2024). Methodology : Four quantitative parameters––Bollinger Bands, intramonthly returns, frequency of intramonthly returns, and beta values––were examined for four actively traded Indian penny stocks (Suzlon Energy Ltd., Comfort Intech Ltd., Vivanta Industries Ltd., and Veeram Securities Ltd.) from 2004 to 2024. The measurements were incorporated into a new combined volatility factor index (CVFI) to systematically evaluate risk–return profiles. Findings : Comfort Intech Ltd. was identified as the most appropriate choice, demonstrating the highest risk and return (CVFI = 4), subsequently followed by Suzlon Energy Ltd. (CVFI = 3) and Vivanta Industries Ltd. (CVFI = 3). Strategic trading opportunities emerged at points where the correlation between price and return diminished, as revealed by Suzlon’s closing price of ₹ 394.71, which resulted in a return of 0.36%. Practical Implications : The CVFI framework equipped investors with a data-driven tool for penny stock evaluation while assisting regulators in monitoring market volatility. Brokerages could use these insights to educate retail investors about risk management in high-volatility segments. Originality : The results of the study reflected the potential of the newly designed robust platform for multidimensional volatility assessment for Indian penny stocks, mitigating a significant gap in emerging market research. CVFI is based on the integration of both technical and fundamental indicators for a comprehensive analysis of candidates for a penny stock portfolio.